Raman spectra of proton order of thin ice Ih film. (4th March 2015) - Men, Zhiwei; Fang, Wenhui; Wang, Shenghan; Li, Zhanlong; Sun, Chenglin; Wang, Xiaojun
<x xml:space="preserve">Abstract</x> The polarized Raman spectra of the upper part of a thin ice Ih film were obtained in the range of 150 cm−1 to 3800 cm−1. The spectra showed clear polarization dependence; several new peaks were also observed. The longitudinaloptic–tranverseoptic (LO–TO) splitting of the mode near 220 cm−1 in the translational vibration region was experimentally confirmed at 133 K. The Fermi resonance between the bending overtone (around 3270 cm−1) and symmetry stretching fundamental (around 3350 cm−1) in the stretching vibration region appeared at nearly the same temperature. Results showed that ice XI (i.e. proton‐ordered phase of ice Ih) slowly formed in the upper part of a thin ice Ih film without KOH as the temperature gradually decreased below 133 K. Copyright © 2015 John Wiley & Sons, Ltd.